Cancer cell membrane coated silica nanoparticles loaded with ICG for tumour specific photothermal therapy of osteosarcoma - Jingwei Zhang; Yu Miao; Weifeng Ni; Haijun Xiao; Jieyuan Zhang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Photothermal therapy (PTT) is a rapidly developing approach for cancer therapy, which has been widely recognized to exert high efficacy as compared to chemotherapy. However, the limited tumour homing property of currently available drug delivery systems (DDSs) is the bottleneck for the efficient delivery of photothermal agents. Here in this study, we surface modified silica nanoparticles (SLN) with the cell membrane (CM) derived from 143B cells to construct a platform (CM/SLN) capable of targeting the homogenous 143B cells. In addition, indocyanine green (ICG) as a photothermal agent was encapsulated into CM/SLN to finally construct a DDS suitable for tumour-targeted PTT of osteosarcoma. Our results revealed that CM/SLN/ICG was mono-dispersed core-shell nanoparticles with advanced stability in a physiological environment. Moreover, due to the modification of CM, CM/SLN/ICG could specifically target the homogenous 143B cells both in vitro and in vivo, which demonstrated superior anticancer efficacy when compared with either SLN/ICG or free ICG. Hence, CM/SLN/ICG could be a promising DDS for tumour targeted PTT of osteosarcoma.